2020
DOI: 10.1149/1945-7111/abc0a5
|View full text |Cite
|
Sign up to set email alerts
|

Review—Thermal Safety Management in Li-Ion Batteries: Current Issues and Perspectives

Abstract: Approaches for thermal management of lithium-ion (Li-ion) batteries do not always keep pace with advances in energy storage and power delivering capabilities. Root-cause analysis and empirical evidence indicate that thermal runaway (TR) in cells and cell-tocell thermal propagation are due to adverse changes in physical and chemical characteristics internal to the cell. However, industry widely uses battery management systems (BMS) originally designed for aqueous-based batteries to manage Li-ion batteries. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 75 publications
(128 reference statements)
0
9
0
Order By: Relevance
“…revealed that the current advanced battery management systems (BMS) are even not capable of preventing the thermal runaway, which is the culprit for the safety issue of lithium‐ion batteries; they also indicated that the incapability of the BMS is because it cannot track the “fast‐emerging” adverse event inside a cell. [ 58 ] This implies that a mild exothermic process even with a lower exothermic peak temperature may be more beneficial for the safety of batteries than an aggressive heat release process (“fast‐emerging” adverse event) with a higher exothermic temperature since it allows more time for the BMS to sensor temperature changes and take actions to prevent unwanted catastrophic burning or explosion. [ 58,59 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…revealed that the current advanced battery management systems (BMS) are even not capable of preventing the thermal runaway, which is the culprit for the safety issue of lithium‐ion batteries; they also indicated that the incapability of the BMS is because it cannot track the “fast‐emerging” adverse event inside a cell. [ 58 ] This implies that a mild exothermic process even with a lower exothermic peak temperature may be more beneficial for the safety of batteries than an aggressive heat release process (“fast‐emerging” adverse event) with a higher exothermic temperature since it allows more time for the BMS to sensor temperature changes and take actions to prevent unwanted catastrophic burning or explosion. [ 58,59 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 58 ] This implies that a mild exothermic process even with a lower exothermic peak temperature may be more beneficial for the safety of batteries than an aggressive heat release process (“fast‐emerging” adverse event) with a higher exothermic temperature since it allows more time for the BMS to sensor temperature changes and take actions to prevent unwanted catastrophic burning or explosion. [ 58,59 ]…”
Section: Resultsmentioning
confidence: 99%
“…While it is challenging to measure the battery calorific rate in the actual operating conditions (usually obtained from accelerating rate calorimetry), empirical and semiempirical modelings are more practical than the experimental thermal modeling methods. [ 233 ] Taking empirical models, for example, Wang and co‐workers developed an improved semiempirical model for accurate and simple heat estimation of the battery. [ 234 ] Experimentally based fitting equations, which determine the ohmic heat and the entropy change heat (and empirical formula derived from an approximate model of lithium diffusion process which calculates the polarization heat), are combined to deliver high accuracy in temperature and voltage modeling of prismatic lithium‐ion batteries.…”
Section: Multiscale Model Applicationmentioning
confidence: 99%
“…In recent reviews, most of the hard sensors that are commonly used in battery management systems (BMS) are presented by Srinivasan et al (2020); Liu et al (2019); Xiong et al (2018), while Raijmakers et al (2019); Ma et al (2018) discussed various hard sensors used in lithium-ion batteries (LIBs), and Liao et al (2019) summarized thermal runaway monitoring techniques. Although there are individual studies that are done on soft sensing in LIBs, there are no reviews on soft sensors for LIBs known to the authors.…”
Section: Introductionmentioning
confidence: 99%